STRATEGI PEMASARAN MELALUI PENETAPAN PROMOSI PENJUALAN DAN KUALITAS PELAYANAN PADA KAFE FORTUNA DI SITUBONDO - Novia, Rozana Putri; Rachman, Riza; Hamida, Lutfiyatil; Sari, Putri Ayu Purnama; H.R.M, Farukh Abdullah; Rahman, Ervina Adita (Fakultas Ekonomi dan Bisnis, 2022)
Fortuna Cafe is one of the cafes in Situbondo Regency. IM Cafe carries out several sales promotions to increase its sales. Sales promotion is an activity implemented for the purpose of increasing sales and increasing consumer demand. And service quality can be defined as anything that focuses on efforts to fulfill consumer needs and desires accompanied by accuracy in conveying them so as to create a balanced conformity with consumer expectations. This research is research using qualitative methods. Data collection was carried out through observation and interviews. Data analysis methods include data condensation, data presentation, and drawing conclusions. The conclusion of this research is that Baliwa Kafe Fortuna carries out various ways of promoting sales and service quality as its marketing strategy. These sales promotion strategies include sales promotions using products and using discounts and service quality indicators, namely real reliability, responsiveness, guarantee and empathy are all indicators of high quality service. The study shows that sales promotion marketing strategies and high quality service will have a significant impact on consumer satisfaction.